Digital Epistemology: How Technology Changes the Way We Understand Mental Health - Al Rasyidah, Putri Febrina; Chasanah, Finanda Puteri; Ramadan, Dwi Hasta Wahyu; Ramadan, Dwi Hasta Wahyu (Maliki Interdisciplinary Journal, 2026)
In general, the development of the digital era has transformed how society understands and verifies information related to mental health. This review maps the shifts in digital epistemology that occurred in Indonesia between 2020 and 2025. Its main focus is on how technology reshapes knowledge sources, information authority, and the ways people determine truth. The method employed in this article is qualitative library research grounded in an interpretive–constructivist paradigm. The study examines several relevant publications using thematic analysis, in-depth interpretation, and conceptual synthesis. The findings reveal three major shifts: the transfer of authority from professional experts to social media and popular content; the role of algorithms in determining the perceived credibility of information; and the increasing use of digital data and artificial intelligence as personal reference points. The reviewed evidence also shows that popularity and emotional resonance influence public trust more strongly than scientific validity, particularly among adolescents and university students. In conclusion, digital epistemology expands access to knowledge while simultaneously heightening the risk of misinformation. Therefore, critical digital literacy and ethical regulation have become essential.